Integration challenges of pure operation-based CRDTs in redis - Younes, Georges (2016)
Pure operation-based (op-based) Conflict-free Replicated Data Types (CRDTs) are generic and very efficient as they allow for compact solutions in both sent messages and state size. Although the pure op-based model looks promising, it is still not fully understood in terms of practical implementation. In this paper, we explain the challenges faced in implementing pure op-based CRDTs in a real system: the well-known in-memory cache key-value store Redis. Our purpose of choosing Redis is to implement a multi-master replication feature, which the current system lacks. The experience demonstrates that pure op-based CRDTs can be implemented in existing systems with minor changes in the original API.